2022
DOI: 10.3390/polym14061078
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gas Counter Pressure on the Surface Roughness, Morphology, and Tensile Strength between Microcellular and Conventional Injection-Molded PP Parts

Abstract: Microcellular injection-molded parts have surface defect problems. Gas counter pressure (GCP) is one of the methods to reduce surface defects. This study investigated the effect of GCP on the surface roughness, morphology, and tensile strength of foamed and conventional injection-molded polypropylene (PP) products. GCP is generated by filling up the mold cavity with nitrogen during the injection-molding (IM) process. It can delay foaming and affect flow characteristics of microcellular and conventional injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The main idea of this approach is to transform the response function into a suitable function and then optimize it. The overall desirability function was synthesized from the expectation functions of each response [54][55][56]. The object here maximizes the overall desirability function.…”
Section: Multi-response Optimizationmentioning
confidence: 99%
“…The main idea of this approach is to transform the response function into a suitable function and then optimize it. The overall desirability function was synthesized from the expectation functions of each response [54][55][56]. The object here maximizes the overall desirability function.…”
Section: Multi-response Optimizationmentioning
confidence: 99%
“…This process effectively suppresses gate‐nucleated bubbles during the filling stage, and nucleation occurs only after the gas release‐induced pressure drops. GCP prevents foaming during the filling stage, enhancing surface quality without the cost of extended cooling time due to additional increments of the mold temperature 30,31 . Lee et al 32 proposed the integration of GCP with the core‐back process for producing high‐quality foamed components.…”
Section: Introductionmentioning
confidence: 99%
“…The second approach is to stop bubbles from getting trapped between the mould cavity and melt in the filling stage. Techniques, such as gas counter pressure (GCP) system [ 13 , 14 , 15 , 16 , 17 , 18 ], gas-assisted microcellular injection moulding (GAMIM) [ 19 ] and pressure-temperature (P-T) control system [ 20 , 21 ], were developed based on this principle by increasing the mould cavity pressure to a certain level at the beginning of the filling stage. It was also reported that both GCP technology [ 22 ] and GAMIM [ 19 ] can improve mechanical properties by increasing solid skin thickness.…”
Section: Introductionmentioning
confidence: 99%